Dynamic modulation of electronic properties of graphene by localized carbon doping using focused electron beam induced deposition. Issue 36 (25th August 2015) - Kim, S.; Russell, M.; Henry, M.; Kim, S. S.; Naik, R. R.; Voevodin, A. A.; Jang, S. S.; Tsukruk, V. V.; Fedorov, A. G.
Abstract : We report on the first demonstration of controllable carbon doping of graphene to engineer local electronic properties of a graphene conduction channel using focused electron beam induced deposition (FEBID). Abstract : We report on the first demonstration of controllable carbon doping of graphene to engineer local electronic properties of a graphene conduction channel using focused electron beam induced deposition (FEBID). Electrical measurements indicate that an "n–p–n" junction on graphene conduction channel is formed by partial carbon deposition near the source and drain metal contacts by low energy (<50 eV) secondary electrons due to inelastic collisions of long range backscattered primary electrons generated from a low dose of high energy (25 keV) electron beam (1 × 10 18 e − per cm 2 ). Detailed AFM imaging provides direct evidence of the new mechanism responsible for dynamic evolution of the locally varying graphene doping. The FEBID carbon atoms, which are physisorbed and weakly bound to graphene, diffuse towards the middle of graphene conduction channel due to their surface chemical potential gradient, resulting in negative shift of Dirac voltage. Increasing a primary electron dose to 1 × 10 19 e − per cm 2 results in a significant increase of carbon deposition, such that it covers the entire graphene conduction channel at high surface density, leading to n-doping of graphene channel. Collectively, these findings establish a unique capability of FEBID technique to dynamically modulate the doping state of graphene, thus enabling a new route to resist-free, "direct-write" functional patterning of graphene-based electronic devices with potential for on-demand re-configurability.